Corporeidade e humanescência: cenários ludopoiéticos na vida de professores contadores de história - Camara, Maria das Dores da Silva Timoteo da (2013)
During the latest years, the art of storytelling has received special attention from those who make education, art and culture. The storyteller is a singular person who manages to seduce itself and its listeners, by involving them in an atmosphere of pleasure and complicity, dodging situations, space and time, providing delight, stimulating creativity, daydreaming and imagination. This is a study developed with storyteller teachers that takes as its starting point the need to change the landscape of education, which seeks to emphasize the affirmation of embodiment of the teacher, so that it participates in a creative self-dynamic and the context in which they live. In addition , the following purposes accompanied the study : education - liberating practice and human development ; corporality - radiant , first and main focus of educational criteria; playfulness - a human dimension ; autopoiese - as an organization of human beings that produces and continuously transforms itself; flow experience concerns the feeling of full involvement in the activity , the psychic energy toward something that is being produced or performed , something that brings us pleasure , happiness and profound sense of well being. As general objective of the study we analysed the humanescent self-formation and its ludopoiética nature in storyteller teachers from humanescent workshops developed in a state school in Natal / RN. In view of the overall objective , we developed the following specific objectives : to identify the ludopoiéticas properties of self-worth , self-connectivity , self-territoriality , autotelia and self realization present in the life of storyteller teachers and the changes in the school environment, from the development of humanescent workshops; reveal the nature of humanescent self-training in storyteller teachers lives. The investigated group had the participation of eight teachers, and had the Escola Estadual Potiguassu as environment for the research. This is a descriptive study, understood as an action-research , developed with basis in the fundamentals and ethnomethodological principles , which used eight humanescents workshops , developed in the context of humanescent experiential pedagogy in conjunction with participant observation .The analyzes were focused on the chosen categories for the study : self-worth , self-connectivity , self-territoriality , autotelia and self-, indexicality and reflexivity . In terms of conclusions, we noted that the properties of ludopoiese were unveiled in the lives of the teachers by providing changes in their ways of being and living together. The teachers have become more creative and intensely began to experience their own life, social life, as well as its meaning. The struggle for a more cheerful and happy school was another important development highlighted in the reports of the teachers, also observing that there was a significant improvement in the reduction of violence in the school environment. Thus, we emphasize that the teachers began to recognize themselves like being ludic, playing with the beauty of storytelling and life